2012
DOI: 10.1016/j.jmb.2012.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of MALT1 Protease Activity

Abstract: The formation of the CBM (CARD11-BCL10-MALT1) complex is pivotal for antigen-receptor-mediated activation of the transcription factor NF-κB. Signaling is dependent on MALT1 (mucosa-associated lymphoid tissue lymphoma translocation protein 1), which not only acts as a scaffolding protein but also possesses proteolytic activity mediated by its caspase-like domain. It remained unclear how the CBM activates MALT1. Here, we provide biochemical and structural evidence that MALT1 activation is dependent on its dimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
151
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(167 citation statements)
references
References 47 publications
13
151
0
3
Order By: Relevance
“…First, the MALT1 paracaspase dimerizes, but is retained in an inactive state by Ig3-mediated auto-inhibition. Second, substrate binding induces structural rearrangements that release the paracaspase from auto-inhibition (Wiesmann et al, 2012). The two-step activation model was confirmed by the identification of allosteric small molecule MALT1 inhibitors, which prevent the conformational rearrangement required for activation by binding to a hydrophobic pocket formed at the interface of the paracaspase and Ig3 domains ( Schlauderer et al, 2013).…”
Section: Malt1 -A Scaffold and A Proteasementioning
confidence: 86%
See 2 more Smart Citations
“…First, the MALT1 paracaspase dimerizes, but is retained in an inactive state by Ig3-mediated auto-inhibition. Second, substrate binding induces structural rearrangements that release the paracaspase from auto-inhibition (Wiesmann et al, 2012). The two-step activation model was confirmed by the identification of allosteric small molecule MALT1 inhibitors, which prevent the conformational rearrangement required for activation by binding to a hydrophobic pocket formed at the interface of the paracaspase and Ig3 domains ( Schlauderer et al, 2013).…”
Section: Malt1 -A Scaffold and A Proteasementioning
confidence: 86%
“…Despite lower sequence homology, caspases are the closest homologs in mammals and the crystal structure of the MALT1 paracaspase-Ig3 domain underscores the conservation. As for classical caspases, the paracaspase domain dimerizes and Cys464 and His415 form a catalytic dyad in the active substrate bound conformation (Yu et al, 2011;Wiesmann et al, 2012). However, whereas caspases cleave substrates after Asp, MALT1 stringently requires Arg in the P1 site, which resembles the Arg/Lys specificity of metacaspases (Hachmann et al, 2012).…”
Section: Malt1 -A Scaffold and A Proteasementioning
confidence: 99%
See 1 more Smart Citation
“…Upon antigen stimulation, the B-cell receptor-associated scaffold protein CARD-containing MAGUK protein 1 (CARMA1), also known as caspase recruitment domain-containing protein 11 (CARD11), is activated to recruit B-cell lymphoma/leukemia 10 (BCL10) and MALT1 forming CARMA1-BCL10-MALT1 (CBM) signallosome via two Ig domains at the amino terminus of MALT1 (refs 3,7-9). The wild-type MALT1 protein has been found to be an argininespecific protease by peptide library screening 10 and supported by structural data 11,12 . In this regard, MALT1 through its paracaspase domain exhibits proteolytic activity by targeting arginine residues of its substrates, tumour necrosis factor alphainduced protein 3 (TNFAIP3), also referred to as A20 (ref.…”
mentioning
confidence: 84%
“…The crystal structure of the MALT1 caspase-like domain further provided clues about the mechanism of MALT1 activation: in the absence of stimulation, MALT1 is not active by itself, since the caspase-like domain is autoinhibited by its interaction with the Ig3 domain. Its activation requires a first dimerization step and a second step in which caspase substrate binding causes substantial structural reorganization, allowing the release of the caspases like domain of MALT1 from the Ig3 inhibitory domain [35]. Using mice lacking MALT1, two different studies reported impaired TCR-mediated NF-κB activation, defective lymphocyte proliferation and decreased IL-2 production (Table 1).…”
Section: Pdk1mentioning
confidence: 99%